RANCANG BANGUN ALAT UJI THRUST MOTOR BRUSHLESS DENGAN VARIASI PROPELLER - Haqqah Risath Mas Intan; Muhammad Luqman Bukhori; Sabri Alimi (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
In drone design, the selection of components such as batteries, Electronic Speed ​​Controllers and propellers must be in accordance with the requirements, but not all components in the RC include measurement data to determine the specifications of the brushless motor. Therefore, a test tool is needed that can calculate the amount of thrust or use a tool trials. Brushless motors and propellers are important components that affect flying performance on drones. The greater the thrust generated by the brushless motor and propeller, the greater the load that can be lifted by the drone. The types of propellers commonly used in drones include 6x4, 9x6, and 10x5 propellers. To measure the amount of thrust, load sensors and current sensors can be used which are converted by the ADC HX711 converter. The test bench tool can be used to produce data experimentally using the help of the sensor. In testing the 6x4e propeller produced a current of 7.8 Ampere and a thrust of 1.13 kgf, the 9x6e propeller produced a current of 16.4 Ampere and a thrust of 1.63 kgf, and the propeller 10x5e produced a current of 18.6 Amperes and a thrust of 2.07 kgf with the right selection of brushless motors and propellers, drone performance can increase.